Characterization of Soils of Ifite Ogwari Campus of Nnamdi Azikiwe University, Anambra State, South Eastern Nigeria (e-Proceedings of the Faculty of Agriculture International Conference, 2023)
This study assessed the properties of soils under arable (profile 1), pasture (profile 2) and forested (profile 3) lands at Nnamdi Azikiwe University Ifite Ogwari campus (latitude 06° 60' 13" N and longitude 6° 95' 63" E) to investigate the morphological, physical and chemical properties and determine relationships among them. A total of 12 samples were collected according to horizon differentiation. Soil samples were examined using standard laboratory procedures and data generated were analyzed using coefficient of variation and correlation to determine their relationships. Textural class of arable and pasture lands ranged from loam to sandy loam and forested land from loamy sand to sandy loam. Mottles colour were observed in pasture and forested lands. Variability in pH of arable, pasture and forested lands was 3.85 %, 3.64 % and 0.90 % respectively. The coefficient of variation of organic carbon content was 16.99 %, 39.59 % and 52.50 % in arable, pasture and forested lands respectively. The variability in base saturation was low in arable land (15.24 %) and pasture land (15.12 %) and moderate in forested land (26.88 %). The Organic carbon content correlated with Total nitrogen (TN) and Available phosphorus (AP) in arable and pasture lands and TN, AP and Na in forested land. The soils have low nutrient reserves and use of organic soil fertility management (dungs and composts) was recommended for farmers to increase yields in arable land, improve pasture land and conserve forested land.
Keywords: Arable land; Forested land; Ifite-Ogwari; Pasture land; Soil properties